1974
DOI: 10.1104/pp.54.4.564
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Characterizing the Relation between Nutrient Concentration and Flux into Roots of Intact Plants

Abstract: A method based on the rate of depletion of a nutrient from solution was developed to characterize nutrient flux of plant roots. Nutrient concentration of the solution was measured at a series of time intervals to describe the complete depletion curve. An integrated rate equation, based on a Michaelis-Menten model, was developed and fit to the data of the depletion curve using a least-square procedure. The A procedure was also developed to measure uptake rate at constant concentration by adding nutrients to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
191
0
10

Year Published

1981
1981
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(204 citation statements)
references
References 8 publications
3
191
0
10
Order By: Relevance
“…Determination of the kinetic parameters V max , K m and, C m was based on the principle proposed by Claassen and Barber (1974), which involves quantifying the reduction in nutrient concentration in the solution resulting from the uptake by the plants. For this, aliquots of 10 mL were removed from the depletion solution, the first being collected at "time zero," before adding the seedlings, and the others at intervals of one hour over a period of 12 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of the kinetic parameters V max , K m and, C m was based on the principle proposed by Claassen and Barber (1974), which involves quantifying the reduction in nutrient concentration in the solution resulting from the uptake by the plants. For this, aliquots of 10 mL were removed from the depletion solution, the first being collected at "time zero," before adding the seedlings, and the others at intervals of one hour over a period of 12 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Short-term results obtained by the use of '•'N and '^N are usually in agreetnent (Clarkson et al, 1996), Kinetic paratneters have also been derived on the basis of tneasuretnents of the rate of depletion of NO3" or NH4^ tVotn the nutrient solution surrounding the roots (e.g. Claassen & Barber 1974; Van de Dijk et al 1982;Goyal & Huffaker 1986), Since the latter tnethod is not able to distinguish between added or effluxed NO," and NH4' *^, it provides data for net uptake, not influx, of NO3" and NH/, Information on differences in competitive nutrient uptake relations in mixtures of legumes and grass species is limited. Rao et al (1993) reported that some non-nodulated legumes (Cicer arietinitn L., Cajatius cajan and Aractiis hypogaea L.) had a higher affinity (lower K,J and a higher maximum net influx (V^ax) for NH4"^ than did cereals (Sorgttuni hieotor, Pennisetum glaucim and Zea mays L.).…”
Section: Introductionmentioning
confidence: 99%
“…Os parâmetros cinéticos foram determinados pelo princípio descrito por Claassen & Barber (1974), o qual consiste em quantificar a diminuição da concentração da solução de acordo com a absorção. Esses parâmetros foram avaliados 14 dias após o transplante das plantas para N, P e K, e 20 dias após o transplante para Ca e Mg, em plantas com 20 e 26 dias respectivamente.…”
Section: Methodsunclassified
“…Os valores dos parâmetros cinéticos (I max , K m e C min ) foram calculados por meio do programa 'software' Cinética (Ruiz, 1985), que se baseia no princípio desenvolvido por Claassen & Barber (1974). Esse programa calcula o I max por meio de uma equação linear, e o K m por equações do tipo exponencial, potencial ou exponencial-recíproco.…”
Section: Methodsunclassified